The Effectiveness of Google Classroom in the Flipped Class-room Model for English Subjects in Vocational School (Universitas Negeri Semarang, 2022)
The purpose of this study is to determine the effectiveness of Google classroom as an e-learning-based learning medium in the Flipped Classroom model to improve student learning outcomes in English subjects at Ibu Kartini Vocational High School, Semarang City. The research method used in this study was quantitative approach, a quasi-experimental design with a non-equivalent control group design model. The sample selection of this research is simple random sampling technique. The tool used to collect data in this study was a test with 50 multiple choice questions. The data analysis technique used is the independent sample t-test and the N-gain score test. The results of the hypothesis test showed that there was a significant difference in learning outcomes between the experimental class and the control class. It means that the use of Google classroom as an e-learning-based learning medium in the Flipped Classroom model proved effective in improving students' learning outcomes. Abstrak Penelitian ini bertujuan mengetahui sejauh mana keefektifan Google classroom sebagai media pembelajaran berbasis e-learning dalam model Flipped Classroom untuk meningkatkan hasil belajar siswa pada mata pelajaran bahasa inggris di SMK Ibu Kartini kota Semarang. Penelitian ini menggunakan pendekatan kuantitatif dengan metode penelitian eksperimen. Desain penelitian ini menggunakan pola quasi experimental design dengan model non-equivalent control group design. Pemilihan sampel penelitian ini dengan teknik simple random sampling. Alat yang digunakan untuk mengumpulkan data pada penelitian ini adalah Tes dengan soal pilihan ganda sebanyak 50 butir soal. Teknik analisis data yang digunakan yaitu uji independent sampel t-test dan uji N-gain score. Hasil uji hipotesis menunjukkan adanya perbedaan yang signifikan hasil belajar antara kelas eksperimen dan kelas kontrol. Dengan demikian dapat disimpulkan bahwa pemanfaatan Google classroom sebagai media pembelajaran berbasis e-learning dalam model Flipped Classroom terbukti efektif meningkatkan hasil belajar siswa pada mata pelajaran bahasa Inggris.